Daily oral iron supplementation during pregnancy - Peña-Rosas, Juan Pablo (Cochrane Database Syst Rev, 2012)
BACKGROUND: Iron and folic acid supplementation has been the preferred intervention to improve iron stores and prevent anaemia among pregnant women, and it may also improve other maternal and birth outcomes. OBJECTIVES: To assess the effects of daily oral iron supplements for pregnant women, either alone or in conjunction with folic acid, or with other vitamins and minerals as a public health intervention. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (2 July 2012). We also searched the WHO International Clinical Trials Registry Platform (ICTRP) (2 July 2012) and contacted relevant organisations for the identification of ongoing and unpublished studies. SELECTION CRITERIA: Randomised or quasi-randomised trials evaluating the effects of oral preventive supplementation with daily iron, iron + folic acid or iron + other vitamins and minerals during pregnancy. DATA COLLECTION AND ANALYSIS: We assessed the methodological quality of trials using standard Cochrane criteria. Two review authors independently assessed trial eligibility, extracted data and conducted checks for accuracy. MAIN RESULTS: We included 60 trials. Forty-three trials, involving more than 27,402 women, contributed data and compared the effects of daily oral supplements containing iron versus no iron or placebo. Overall, women taking iron supplements were less likely to have low birthweight newborns (below 2500 g) compared with controls (8.4% versus 10.2%, average risk ratio (RR) 0.81; 95% confidence interval (CI) 0.68 to 0.97, 11 trials, 8480 women) and mean birthweight was 30.81 g greater for those infants whose mothers received iron during pregnancy (average mean difference (MD) 30.81; 95% CI 5.94 to 55.68, 14 trials, 9385 women). Preventive iron supplementation reduced the risk of maternal anaemia at term by 70% (RR 0.30; 95% CI 0.19 to 0.46, 14 trials, 2199 women) and iron deficiency at term by 57% (RR 0.43; 95% CI 0.27 to 0.66, seven trials, 1256 women). Although the difference between groups did not reach statistical significance, women who received iron supplements were more likely than controls to report side effects (25.3% versus 9.91%) (RR 2.36; 95% CI 0.96 to 5.82, 11 trials, 4418 women), particularly at doses 60 mg of elemental iron or higher. Women receiving iron were on average more likely to have higher haemoglobin (Hb) concentrations at term and in the postpartum period, but were at increased risk of Hb concentrations greater than 130g/L during pregnancy and at term. Twenty-three studies were conducted in countries that in 2011 had some malaria risk in parts of the country. In some of these countries/territories, malaria is present only in certain areas or up to a particular altitude. Only two of these reported malaria outcomes. There is no evidence that iron supplementation increases placental malaria. For some outcomes heterogeneity was higher than 50%. AUTHORS’ CONCLUSIONS: Prenatal supplementation with daily iron are effective to reduce the risk of low birthweight, and to prevent maternal anaemia and iron deficiency in pregnancy. Associated maternal side effects and particularly high Hb concentrations during pregnancy at currently used doses suggest the need to update recommendations on doses and regimens for routine iron supplementation.